Identifikasi Mikoriza Vesikular Arbuskular (MVA) dari Rhizosfer Bawang Merah (Allium cepa L.) dan Talas (Colocasean esculenta (L.) Schott) serta Perbanyakannya Menggunakan Media Zeolit - NI WAYAN ARMINI; I GEDE PUTU WIRAWAN; I NYOMAN WIJAYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2015)
ABSTRACT Vesicular Arbuscular Mycorrhizae (VAM) Identification of Red Onion (Allium cepa L.) and Taro (Colocasean esculenta (L.)Schott) Rhizosphere and Its Spore Multiplication in Zeolite Media Efforts to increase agricultural production can be done with a variety of technologies. Technology is widely applied to farmers in the cultivation process is the use of inorganic fertilizers with high doses exceeding the dose of balanced fertilizer. In the production of onion crops in the field, also using inorganic fertilizer application on an ongoing basis which may result in damage to the ground both in terms of texture and structure. Red onions and taro roots are shallow causing both of these plants are unable to absorb nutrients to the maximum if exercised enough chemical fertilizer. This study was aimed to determine genus and species of VAM in red onion and taro rhizosphere, its colonization in root tissue, and to examine zeolite media compatibility with corn as a symbiont. Based on the results of the study, it was found three species of VAM spores of red red onion plant rhizosphere, namely: Acaulospora denticulata, A. laevis, Glomus ambisporum, and five species of VAM spores recovered from the rhizosphere of taro plants namely: Acaulospora foveata, A. koskei, A. capsicula, Scutellospora calospora and Glomus ambisporum. Infections were found in plants onion, taro and corn plants form symbiotic arbuscular, vesicles and inner spore. VAM from the rhizosphere of plants onion and taro can be reproduced using zeolite media and symbionts plant corn. Keywords: MVA, rhizosphere, Acaulospora, zeolite, inner spore